An Open Educational Resource Supports a Diversity of Inquiry-Based Learning - Schmidt-Jones, Catherine Anne (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2012)
There have been numerous calls for research that demonstrates how open education resources (OERs) are actually being used. This case study sought to shed light on the users of a well-visited set of modular music-education materials published at Connexions. Respondents to a voluntary survey included teachers, students, self-directed learners, music ensemble participants, and casual learners. Most reported accessing individual modules on their own initiative, as part of a specific, immediate inquiry, rather than responding to institutional directives or following entire online courses. This was supported by computer-log records, which showed that most visitors to a module arrived from an Internet search for terms specific to that module. The study suggests that, for teachers and students as well as self-directed learners, one function of OERs is as a resource for just-in-time, inquiry-based learning.